The Eight-Year Study: From Evaluative Research to a Demonstration Project, 1930—1940. - Watras, Joseph (Education Policy Analysis Archives, 2006)
From 1932 to 1940, the Progressive Education Association (PEA) conducted its Eight-Year Study. At first, the study appeared to be a poorly funded comparison of two groups of students in secondary schools. During the last four years, as more financial support became available, the Eight-Year Study became a broadly based demonstration of a wide range of educational innovations. For contemporary educators, the story of the Eight-Year Study represents an opportunity to reconsider popular principles of program evaluation such as utilization-focused evaluation or program theory in evaluation. Rather than set plans in advance, the PEA members seemed to follow the ideas of John Dewey; they allowed the purposes to widen and broaden as the study evolved. In this way, the Eight-Year Study represented a model of democratic policy evaluation. Its tentative type of planning allowed people to set and to change their own purposes in line with the needs of the wider organization. Part of the reason that the study changed direction was it gathered more financial support and could add consultants who worked in distinct program elements. In addition, the lack of consistency matched the varied nature that characterized the founding members of the PEA. Its democratic framework may have enabled the Eight-Year Study to become the PEA’s abiding contribution to American education.